2017
DOI: 10.1002/ajoc.201700001
|View full text |Cite
|
Sign up to set email alerts
|

Iodine‐Mediated Sulfonylation of Quinoline N‐Oxides: a Mild and Metal‐Free One‐Pot Synthesis of 2‐Sulfonyl Quinolines

Abstract: A synthetic strategy for an iodine‐mediated sulfonylation of quinoline N‐oxides has been developed. A wide variety of 2‐sulfonyl quinoline derivatives were synthesized by reacting various quinoline N‐oxides with different sodium sulfinates in the presence of sub‐stoichiometric amounts of I2 in one pot, after 2 h at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…Interestingly, Zhao's group found that this reaction could even be performed without TBHP. Moreover, I 2 is an effective activating agent and can be regenerated by air oxidation of the iodide ion produced in the reaction (Scheme 47B) [72] …”
Section: Simple C2‐h‐functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Zhao's group found that this reaction could even be performed without TBHP. Moreover, I 2 is an effective activating agent and can be regenerated by air oxidation of the iodide ion produced in the reaction (Scheme 47B) [72] …”
Section: Simple C2‐h‐functionalizationmentioning
confidence: 99%
“…Moreover, I 2 is an effective activating agent and can be regenerated by air oxidation of the iodide ion produced in the reaction (Scheme 47B). [72] In 2017, an efficient, ultrasound-accelerated onepot synthesis of 2-sulfonylquinolines in water was developed by He's group (Scheme 48). [73] Ultrasound irradiation aided in the zinc-dust-mediated reduction of the sulfonyl chloride to a zinc bissulfinate compound, group later reported a TsCl-promoted aqueous sulfonylation that proceeds via the traditional Reissert-type mechanism (Scheme 49).…”
Section: Organic Reagent/base-promoted Deoxygenative Sulfonylationmentioning
confidence: 99%
“…However, this DABCO‐promoted cyclization reaction employs an unstable starting compound, o ‐alkynylaryl isocyanide, which was synthesized through the dehydration of N ‐formylamide by the use of a harsh reagent, POCl 3 , and a large excess of ( i Pr) 2 EtN (8 equiv.). Recently, quinoline N ‐oxides have been well studied in the selective construction of C2–C, C2–N, and C2–S bonds. Comparatively, there are only few reports in the literature concerning the selective construction of C2–O bonds .…”
Section: Introductionmentioning
confidence: 99%
“…In our previously reports, we described the H ‐phosphonate‐mediated C2‐selective amination, alkylation, and sulfonation of quinoline N ‐oxides towards 2‐substituted quinolines and found that H ‐phosphonate played a key role in the activation of C2–H covalent bonds. [17a], [17b], [18b] Therefore, we continuously committed our efforts to explore our practical methodology for the selective construction of the challenging C2–O bond. Herein, we would like to disclose the highly efficient one‐pot synthetic method for the synthesis of 2‐aroxy(alkoxy)quinolines in the presence of H ‐phosphonate and CCl 4 under mild conditions (Scheme e).…”
Section: Introductionmentioning
confidence: 99%
“…He's group (Scheme 1b) 6 and Zeng's group 7 independently disclosed the reaction of quinoline N-oxides with sulfonyl hydrazides, and a series of the corresponding products was efficiently obtained. In the presence of iodine as catalyst, deoxygenative and regioselective 2-sulfonylation of quinoline N-oxides with sodium sulfinate salts was developed by Zhao's group (Scheme 1c) 8 and Yotphan's group, 9 providing the desired products in moderate to high yield at room temperature. Although various methods for the deoxygenative sulfonylation of quinoline N-oxides have been established, there are few examples providing a method for the direct construction of 2-sulfonylquinolines via a radical pathway.…”
mentioning
confidence: 99%